Production management of digital content for social media in the department of communication and informatic Batang Central Java - Qorin Munandiyal, Qorin Munandiyal Haq; Fajar Junaedi, Fajar Junaedi (Universitas Ahmad Dahlan, 2022)
Covid-19 impacts all sectors, not only the economic, social, cultural sectors but also affects the realm of communication and information. Department of Communication and Information of Batang Regency is one of the local government agencies to provide information services to the people of Batang Regency. With this pandemic, the Department of Communication and Information of Batang Regency is more focused on creating content about Covid-19. This study aims to examine the production management of social digital media content at Department of Communication and Information of Batang Regency. Using descriptive qualitative research by exploring observations at the office and collecting data from the Communication and Information Office of Batang Regency. This study looks at how the production process during the pandemic is limited and continues to run the production process by following health protocols. The content created by the Department of Communication and Informatic of Batang Regency contains messages related to health that are arranged interestingly and can be well received by the Batang people. In publishing content, the Department of Communication and Information of Batang Regency utilizes social media that is often accessed by the Batang Regency community, such as Instagram, Facebook, and YouTube. Before publication, the Department of Communication and Information of Batang Regency media center team continued to consult with the head of the field as the person in charge of content. Published content is infographics, vaccination news, and Public Service Advertisements (PSA).